2014
DOI: 10.1038/nmat4084
|View full text |Cite
|
Sign up to set email alerts
|

Current-induced transition from particle-by-particle to concurrent intercalation in phase-separating battery electrodes

Abstract: Many battery electrodes contain ensembles of nanoparticles that phase-separate upon (de)intercalation. In such electrodes, the fraction of actively-intercalating particles directly impacts cycle life: a vanishing population concentrates the current in a small number of particles, leading to current hotspots. Reports on the active particle population in the phase-separating electrode lithium iron phosphate (LFP) vary widely, ranging from around 0% (particle-byparticle) to 100% (concurrent intercalation). Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
364
3
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 299 publications
(401 citation statements)
references
References 50 publications
29
364
3
5
Order By: Relevance
“…At low current densities, particles transform sequentially, whereas the sequential transformation is suppressed at high current densities (in agreement with Ref. 38, in which a similar transition from sequential to simultaneous transformation is also observed for both the case of two-phase lithiation and the case of suppressed intraparticle phase separation). However, there are some differences between the two cases.…”
Section: Intraparticle Phase Separation-supporting
confidence: 90%
“…At low current densities, particles transform sequentially, whereas the sequential transformation is suppressed at high current densities (in agreement with Ref. 38, in which a similar transition from sequential to simultaneous transformation is also observed for both the case of two-phase lithiation and the case of suppressed intraparticle phase separation). However, there are some differences between the two cases.…”
Section: Intraparticle Phase Separation-supporting
confidence: 90%
“…57,60 Li et al conducted an in-depth characterization and observed that only 5% to 8% of particles are actively intercalating during lithiation, while during delithiation the active population ranges from 8 to 32%. 24 They further confirm that the current is heterogeneously distributed in the electrode, that is to say, only a small number of active particles carries most of the current regardless of the total electrode current. Taking into account that lithiation of Si will not occur until the native silicon oxide is at least partially reduced by Li ions 49 and the gas evolution behavior presented here, we assume that diffusion of Li ions takes place as follows: during lithiation, Li ions that pass though the separator and/or the native Li ions in the native lithium salt electrolyte will first diffuse to the potentially active electrode particles, reduce the electrolyte and/or lithium salts with the obtain of electrons from the electrode and successively reduce the native silicon oxide, thus forming the SEI layer with inorganic inner species and organics outer species, releasing gas, and finally lithiate the active particles of the electrode, leaving non-active local regions intact.…”
Section: Resultsmentioning
confidence: 68%
“…[24][25]56 For example, a discrepancy is observed between electrochemical measurements that represent the overall state of the cell and spectroscopic data that represent a local state. [57][58] A recent experiment by Delmas et al showed the coexistence of fully lithiated and fully delithiated individual LiFePO 4 cathode particles by Xray diffraction after full lithiation.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12] For example, a heterogeneous SOC distribution has recently been reported in spinel LiMn1.5Ni0.5O4 (LMNO) micro-crystals. 13 The evolution of SOC distribution within a LiCoO2 particle upon long term 2 cycling was also reported recently.…”
Section: Introductionmentioning
confidence: 99%